(untitled) (GEOmedia, 2009)
LABSITA between research and applications LABSITA (Land and Environment Information Systems Laboratory) is a ten year old research laboratory designed at the University of Rome "La Sapienza" and lead by Mauro Salvemini, former AM/FM and EUROGI president. As a departmental structure, the laboratory collaborates with CAVEA (Department of Architecture Charachter, Evaluation and Environment) staff lead by prof. Luciano De Licio and include Laura Berardi, Pasquale Di Donato and Valeria Mercadante as researchers, as well as external researchers and consultants who cooperate on certain projects.